NEGATION PREFIXES: DOCUMENT ANALYSIS ON JAKARTA POST THROUGH MORPOLOGICAL ANALYSIS STUDY APPROACH - Gunawan, Triyana; Halimatu Syadiah, Siti Nurhayati; Helmie, Jauhar; Saprudin, Saprudin; Nurviyani, Vina (Universitas Suryakancana, 2025)
The purposes of this study are: 1) to get the types of negative prefixes in The Jakarta Post online newspaper, and 2) to find out which negative prefixes that often appear in The Jakarta Post online news column. The method used in this study is qualitative research and is designed in analysis study. Data were analysed from The Jakarta Post online newspaper using a descriptive analysis method, which involved several steps. First, the newspaper was searched for relevant articles. Next, words containing negative prefixes were collected to identify the types of negative prefixes and their frequency, particularly in economic and political news articles. These activities were carried out on several columns in each edition. The results indicate that negative prefixes play an important role in conveying negative meanings. This occurs in nouns, verbs, adjectives, and adverbs, morphologically and semantically, depending on which part of the word is attached first. Additionally, the study describes the forms, functions, and meanings of the identified prefixes. Morphologically, the affixation processes involving the negative prefixes dis-, un-, in-, mis-, im-, and il- illustrate how these prefixes can change word classes as derivational prefixes.